Butyrylcholinesterase as a marker of inflammation and liver injury in the acute and subclinical phases of canine ehrlichiosis. (December 2015) - do Carmo, Guilherme M.; Crivellenti, Leandro Z.; Bottari, Nathieli B.; Machado, Gustavo; Borin-Crivellenti, Sofia; Moresco, Rafael N.; Duarte, Thiago; Duarte, Marta; Tinucci-Costa, Mirela; Morsch, Vera M.; Schetinger, Maria Rosa C.; Stefani, Lenita M.; et al.
Highlights: Canine ehrlichiosis is a bacterial disease present in Brazil. The infection by Ehrlichia canis can be asymptomatic or symptomatic. BChE profile might be helpful for better understanding of disease pathogenesis. BChE participates in the modulation of the immune response. Dogs with ehrlichiosis have altered production of hepatic BChE. Abstract: The aim of this study was to evaluate the role of butyrylcholinesterase (BChE) as a marker of inflammation and liver injury in the acute and subclinical phases of canine ehrlichiosis. Forty-two serum samples of dogs naturally infected with Ehrlichia canis were used, of which 24 were from animals with the acute phase of the disease and 18 with subclinical disease. In addition, sera from 17 healthy dogs were used as negative controls. The hematocrit, BChE activity, hepatic injury (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), nitric oxide, and cytokines levels were evaluated. The BChE activity was significantly elevated ( P  < 0.05) in dogs with the acute phase of the disease when compared to healthy animals. However, there was a reduction on BChE activity on dogs with subclinical disease compared to the other two groups. AST and ALT levels were significantly higher ( P  < 0.05) in the acute phase, as well as the inflammatory mediators (NO x, TNF-α, INF-γ, IL-4, IL-6) when compared to the control group. On the other hand, IL-10 levels were lower in the acute phase. Based on these results, we are able to conclude that the acute infection caused by E. canis in dogs leads to an increase on seric BChE activity and some inflammatory mediators. Therefore, this enzyme might be used as a marker of acute inflammatory response in dogs naturally infected by this bacterium.